EVALUASI SISTEM GENERAL LEDGER DENGAN BERBASIS APLIKASI ABI PRO - Noerlina, Noerlina; Stefanus, Cahyadi W (Bina Nusantara University, 2007)
The running evaluation system has purpose to make sure whether the control in general ledger informationsystem was sufficient enough and also can support an effective and efficient performance. The evaluations are usinginterview, questioner, and observation method. The result was it can be known the positive and negative on every controland running application. The negative thing on application will be put on risk analysis table and also with recommendationon the negative things. The conclusion of the research was measure of the running information system, how far it wasrunning with the control, and the important of the company awareness to make evaluation on the information systemcontrol.Keywords: evaluation, information system, application, general ledger